n = 1 ∑ ∞ ln ( 1 − ( 5 n 1 ) 2 ) = ln ( π a b a − b a )
where a and b are positive integers. Find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how did u obtain the 4th step from the 3rd step?? first 2 steps are clear from euler's equation
Log in to reply
You mean sin 5 π = 8 5 − 5
Log in to reply
yes. could you explain that?
Log in to reply
@Rishabh Bhat – I was using Wolfram Alpha, thinking it was not important part of the solution. I have added a note to explain it. Hope it helps.
Log in to reply
@Chew-Seong Cheong – yes, it does. thank you for the quick response.
n = 1 ∑ ∞ ( lo g ( n 2 ) − lo g ( n 2 − y 2 ) ) = n = 1 ∑ ∞ ∫ 0 y n 2 − x 2 2 x d x = ∫ 0 y ( n = 1 ∑ ∞ n 2 − x 2 2 x ) d x = ∫ 0 y x 1 − π x cot ( π x ) d x = lo g ( y csc ( π y ) ) + lo g ( π )
Also, you could use x sin x = n = 1 ∏ ∞ ( 1 − n 2 π 2 x 2 ) at x = 5 π
Beautiful solution
Nice solution. Could you elaborate further on how to get n = 1 ∑ ∞ n 2 − x 2 2 x = x 1 − π x cot ( π x ) .
Log in to reply
@Chew-Seong Cheong - I am pretty sure it is a result from complex analysis. You can use this to prove the product formula for sinc, without the Weierstrass/Hadamard factorization theorems.
Problem Loading...
Note Loading...
Set Loading...
Simple solution thanks to @Jasper Braun
Considering the following identity:
n = 1 ∏ ∞ ( 1 − n 2 π 2 x 2 ) n = 1 ∏ ∞ ( 1 − ( 5 n 1 ) 2 ) n = 1 ∑ ∞ ln ( 1 − ( 5 n 1 ) 2 ) = x sin x = 5 π sin 5 π = ln ( π 5 sin 5 π ) = ln ⎝ ⎛ π 5 8 5 − 5 ⎠ ⎞ Putting x = 5 π See note.
⟹ a + b = 5 + 8 = 1 3
Note:
Using the identity ( see proof ):
cos 5 π + cos 5 3 π cos 5 π − cos 5 2 π cos 5 π − 2 cos 2 5 π + 1 4 cos 2 5 π − 2 cos 5 π − 1 = 2 1 = 2 1 = 2 1 = 0 As cos ( π − x ) = − cos x
Solving the quadratic equation:
cos 5 π ⟹ sin 5 π = 8 2 + 2 0 = 4 1 + 5 = 1 − cos 2 5 π = 8 5 − 5